PERAN SC ( SWISSCONTACT) DALAM PENINGKATAN INDUSTRI PARIWISATA PULAU FLORES (2010-2013) - Purba, Pran Suhandono; Pakpahan, Saiman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This study aims to determine the role of Swisscontact (SC) in the development of the tourism industry on the island of Flores Flores Island in 2010-2013. Swisscontact is one of the non-governmental organization that helps developing countries. One of Swisscontact program is to develop the tourism industry in partner countries. The tourism industry is a social phenomenon, cultural and economic mobility needs of society to the country or place outside their environment for personal or business / professional. Thus, tourism has implications on the economy, the natural environment, local residents and tourists in the destination itself. Currently, the tourism industry became one of the most important economic sector for many countries, especially in Indonesia. The results of this study indicate that the role of Swisscontact in the tourism industry on the island of Flores has shown results. Some roles are created by Swisscontact is through promotional programs to increase tourist visits. Swisscontact also conduct training of human resources and develop the private sector on the island of Flores were entered into the program WiSATA. Not only that Swisscontact also undertake the development of new tourist destinations.Keywords : Swisscontact (SC), Tourism Industry, Promotion, Program WiSATA, Program Develop New Destination.